2005
DOI: 10.1097/01.ju.0000161592.00434.c1
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Reconstitution With Bone Marrow Derived Stem Cells Seeded on Small Intestinal Submucosa Improves Morphological and Molecular Composition

Abstract: Bladder reconstitution occurs more rapidly using stem cell seeded SIS. Although in USG and SSG all 3 cellular constituents appear to develop by 3 months, only SSG had gene expression levels similar to those in controls. The results suggest an explanation for the fibrosis noted in unseeded SIS bladder augmentations and the possible solution using stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 20 publications
2
56
1
Order By: Relevance
“…A similar architecture was also apparent in the control group that was not seeded with MSCs, although a longer duration was required to distinguish the three layers. 37 Although migration of cells from native tissue more than likely contributed to the findings, the transplanted stem cells imparted an observable advantage. However, the responsible mechanism remains to be elucidated.…”
Section: Seeded Cell Type: the Application Of Stem Cellsmentioning
confidence: 95%
“…A similar architecture was also apparent in the control group that was not seeded with MSCs, although a longer duration was required to distinguish the three layers. 37 Although migration of cells from native tissue more than likely contributed to the findings, the transplanted stem cells imparted an observable advantage. However, the responsible mechanism remains to be elucidated.…”
Section: Seeded Cell Type: the Application Of Stem Cellsmentioning
confidence: 95%
“…MSCs were shown to migrate to the bladder grafts and differentiate into smooth muscle cells (Kanematsu et al, 2005). These cells achieved fast repopulation of the grafts, which exhibited appropriate neural function and less fibrosis (Chung et al, 2005 (Zhang et al, 2005), and thus the use of MSCs may help to engineer a bladder when no bladder-derived cells are available. Clinical application of bladder tissue engineering has made important steps; however, more needs to be done in the future to achieve the target of whole-organ regeneration and transplantation in urology.…”
Section: Urinary Tissues -Bladdermentioning
confidence: 99%
“…It is for this reason that bone marrow-derived MSCs are an attractive candidate for bladder tissue regeneration (91). Chung et al (92) reported positive results in healthy rat bladders following the introduction of porcine small intestinal submucosa seeded with MSCs from rat bone marrow. These rats exhibited normal urinary bladder architecture, and histological analysis demonstrated well-differentiated urothelial and smooth muscle cells compared with control experiments using unseeded intestinal submucosa (92).…”
Section: Stem Cells In Bladder Regenerationmentioning
confidence: 99%